A Short history of the Middle East - Kerr, Gordon (Pocket Essentials, 2016)
"Situated at the crossroads of three continents, the Middle East has confounded the ambition of conquerors and peacemakers alike. Christianity, Judaism and Islam all had their genesis in the region but with them came not just civilization and religion but also some of the great struggles of history. This book makes sense of the shifting sands of Middle Eastern history, beginning with the early cultures of the area and moving on to the Roman and Persian Empires; the growth of Christianity; the rise of Islam; the invasions from the east; Genghis Khan's Mongol hordes; the Ottoman Turks and the rise of radicalism in the modern world symbolized by Islamic State" -- Provided by publisher.